PERISTILAHAN TRADISI RAYE KUBBOR PADA MASYARAKAT DESA LUMBANG KECAMATAN SAMBAS KABUPATEN SAMBAS - Auliya', Nuria Zahratul; Patriantoro, Patriantoro; Heryana, Nanang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to classified data obtained from the field, doing a data inventory in the form of terminology, lexical meaning, grammatical meaning, and cultural meaning, as a plan of implementation in Indonesian Language learning based on traditional terminology "Raye Kubbor" in Lumbang Village society, Sambas subdistrict, Sambas district. The method used in this research is descriptive qualitative method. The data source in this research was Malay Sambas society in Lumbang Village. The technique of the data collection used were interview, record, note, observation, and documentation. The data collection tools included list of questions, stationery, note sheet. Data validity techniques include diligent observation, adequacy of references, and guidance with lecturers. This research produced 42 data on terms of the Raye Kubbor tradition in the Lumbang Village society, Sambas District, Sambas Regency with details of 14 terms in the form of shape data including 11 monomorphemic data and 3 polymorphemic data; 20 data on lexical meaning including 9 data on tool and material terminology, 6 data on process terminology, 5 data on food terminology, 3 data on grammatical meaning including 1 data on material terminology, 2 data on process terminology; and 7 cultural meaning data including terminology for tools and materials, food, and processes. The form of the Indonesian language learning text is based on the terminology of the Raye Kubbor tradition in the Lumbang Village community, Sambas District, Sambas Regency, descriptive text.